Flower Development of Heterodichogamous Juglans mandshurica (Juglandaceae) - Zhang, Lijie; Guo, Chong; Lu, Xiujun; Sun, Xiaomei; Liu, Chunping; Zhou, Qiang; Deng, Jifeng (Frontiers in Plant Science, 2021)
Juglans mandshurica is a monoecious heterodichogamous species with protogynous and protandous mating strategies that occur at a 1:1 ratio and are randomly distributed in the population. The inconsistent male and female flowering periods of the same mating type result in an imbalance of the ratio of male and female flowers, contributing to the low yield of this species. However, little more is known about its floral development. Following three consecutive years of observations, histological analysis, and scanning electron microscopy, we found that the morphological and anatomical development of the male and female flowers were synchronous. The male floral morphological development of J. mandshurica was divided into seven phases, while that of the female flower was nine. Four stages were shared between the male and female flower’s anatomical development. Our findings indicate that there was minimal overlap between sexual functions within the same mating type, guaranteeing synchronization, mutual non-interference, outcrossing, and avoidance of self-fertilization. These results provide a theoretical basis for the improvement of fruit yield and quality through the reasonable allocation of protogynous and protandrous individuals in a population, and for artificial pollination control. Further, these findings lay a foundation for further research on the genetic mechanisms and environmental effects on flower development of heterodichogamous J. mandshurica.